Development of an enzymatic encapsulation process for a cycloamylose inclusion complex with resveratrol. (30th May 2021) - Jeong, Hyun-Mo; Lee, Yeontaek; Shin, Yu-Jeong; Woo, Seung-Hye; Kim, Ji-Soo; Jeong, Da-Woon; Shin, Sooyong; Jeon, Sung Ho; Shim, Jae-Hoon
Highlights: A novel cycloamylose (CA)-mediated encapsulation method using CGTase was developed. A CA inclusion complex with resveratrol (RVT) was prepared via CGTase-mediated cyclization. Encapsulation increased the water solubility of RVT approximately 6, 000-fold. The CA-RVT inclusion complex exhibited similar activities as an equal amount of RVT in DMSO. With this encapsulation method, the limited solubility of RVT can be overcome. Abstract: Cyclodextrin glucanotransferase (CGTase; EC 2.4.1.19) produces cycloamyloses (CAs), which are large cyclic glucans, and subsequently transforms them to α-, β-, and γ-cyclodextrins. We developed a novel encapsulation process based on the cyclization activity of CGTase and applied it to the formation of CA inclusion complexes with resveratrol (RVT), which has limited bioavailability due to its low water solubility. The encapsulated RVT (CA-RVT) was purified using preparative high-performance liquid chromatography. The water solubility of CA-RVT was 6, 000-fold higher than that of RVT. CA-RVT in water demonstrated 98% stability for 1 week at 4 °C. According to radical scavenging activity and anti-inflammatory assays, CA-RVT in aqueous solution exhibited similar activities as an equal amount of RVT in dimethyl sulfoxide, suggesting the limited solubility of RVT can be overcome through CA encapsulation by CGTase, thus enhancing its nutraceutical value as a functional ingredient in the food industry.